A 'Diversity of Passions and Humours': Early anti-methodist literature as a disguise for heterodoxy. Issue 1 (May 2017) - Lewis, Simon
This article explores the way in which early anti-Methodist literature was utilised as a disguise for heterodoxy. It draws particular attention to Thomas Whiston, an Anglican divine, who published a polemic in 1740, entitled The Important Doctrines of Original Sin, Justification by Faith, and Regeneration . Whiston advertised this tract as an attack on the Methodists and their perceived ally, William Law. However, this paper argues that anti-Methodism was merely a smokescreen which enabled Whiston to profess his loyalty to the established Church, while he advanced various heterodox views. Whiston's controversial opinions included his rejection of the Augustinian doctrine of original sin, along with his subtle show of support for the annihilationist views which his uncle, William Whiston, had recently expressed in The Eternity of Hell Torments (1740). Crucially, such views were repugnant, not only to Methodists, but also to numerous High Churchmen who similarly despised evangelical 'enthusiasm'.